Effect of growth stages on the changes in bioactive compounds of Nagpur mandarin (Citrus reticulata) fruits of Ambia crops - Ram, Lallan; Kumar, Dinesh (The Indian Journal of Agricultural Sciences, 2012)
The fruits of Nagpur Mandarin Ambia crops were analyzed for the changes in bio-active compounds. About 45.4% processing waste as peel, rag and seed can be used for byproduct development. However, TSS increased gradually from 6.45% (marble) to 11.16% (mature fruits).While, acidity dwindles at mature stages (0.69%). The pH of juice ranged between 2.54 and 3.59, indicating that juice remains in acidic state throughout the maturation period. The juice and peel tissues of mature fruits had higher carotene of 0.039 mg/ gfr.wt. and 0.423 mg/g fr.wt than that of juice tissue. The pectin in juice ranged from 0.15 to 1.03 mg/g fr.wt during maturation. Peel oil and oil aldehyde content was recorded higher of 0.75% and 0.93% in the fruits harvested at mature stage. The juice limonin decreased to 5.28 ppm and naringin increased to 110 ppm in the mature stage in ambia crops.